Initial Studies of a Potent Antiheparin Agent (Ubiquin®) - Goodsell, E. B; Krause, R. A; Kimura, E. T (Thrombosis and Haemostasis, 1968)
Ubiquin (oligo-3-(N-methylmorpholinium)-l,2-propylene oxide chloride) is a stable, water soluble, active heparin antagonist producing prompt neutralization when administered in a 1:1 ratio to rats and dogs. Initial studies indicate that it is devoid of any effect on coagulation per se; nor are there any obvious side effects manifested during the process of neutralization. The acute toxicity is less than that of other compounds in use: toluidine blue, protamine and hexadimethrine.